Sedimentary Provenance and Petrogenesis: Perspectives From Petrography and Geochemistry 2007
DOI: 10.1130/2006.2420(14)
|View full text |Cite
|
Sign up to set email alerts
|

Complex examination of the Upper Paleozoic siliciclastic rocks from southern Transdanubia, SW Hungary—Mineralogical, petrographic, and geochemical study

Abstract: A vertical section of Upper Paleozoic sandstones from southern Transdanubia (Mecsek-Villány area, Tisza mega-unit, Hungary) has been analyzed for major and trace elements, including rare earth elements (REEs). In addition, the clay mineralogy of the sandstone samples and the petrography and geochemistry of gneiss and granitoid clasts extracted from the associated conglomerates have been determined. Geochemistry of the sandstone samples analyzed in this study shows that these rocks were predominantly derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 27 publications
0
31
0
11
Order By: Relevance
“…Терригенные породы низов оселковой серии (мар-нинская и нижняя часть удинской свиты) имеют отличные от верхов этой же серии (верхняя часть удинской и айсинская свита) петрохимические ха-рактеристики. Так, на классификационной диа-грамме log(Na 2 O/K 2 O) -log(SiO 2 /Al 2 O 3 ) [Varga et al, 2007], модифицированной после [Pettijohn et al, 1972] (рис. 6) точки составов пород верхней части оселковой серии попали в поля аркозов и лититов, тогда как фигуративные точки пород нижней части оселковой серии сместились от полей субаркозов и аркозов в поле пород, демонстрирующих потерю Nа 2 O [Varga et al, 2007].…”
Section: петрогенные элементыunclassified
See 3 more Smart Citations
“…Терригенные породы низов оселковой серии (мар-нинская и нижняя часть удинской свиты) имеют отличные от верхов этой же серии (верхняя часть удинской и айсинская свита) петрохимические ха-рактеристики. Так, на классификационной диа-грамме log(Na 2 O/K 2 O) -log(SiO 2 /Al 2 O 3 ) [Varga et al, 2007], модифицированной после [Pettijohn et al, 1972] (рис. 6) точки составов пород верхней части оселковой серии попали в поля аркозов и лититов, тогда как фигуративные точки пород нижней части оселковой серии сместились от полей субаркозов и аркозов в поле пород, демонстрирующих потерю Nа 2 O [Varga et al, 2007].…”
Section: петрогенные элементыunclassified
“…6. Классификационная диаграмма log(Na 2 O/K 2 O)-log(SiO 2 /Al 2 O 3 ) для песчаников [Varga et al, 2007], мо-дифицированная после [Pettijohn et al, 1972]. Условные обозначения см.…”
Section: петрогенные элементыunclassified
See 2 more Smart Citations
“…Recently, Varga et al (2001Varga et al ( , 2002Varga et al ( , 2003Varga et al ( , 2007 and reported the mineralogical, petrographic, and chemical composition of these rocks. In this study we include data from clay mineralogical and bulk-rock geochemical analyses of sandstone, sandy siltstone, and conglomerate samples collected from the Upper Carboniferous Téseny Sandstone Formation (Slavonia-Drava Unit, Tisza Mega-unit, Hungary) to describe paleoweathering conditions.…”
Section: Introductionmentioning
confidence: 99%